Analisis Penggunaan IPTEK dalam Pembelajaran Kurirkulum Merdeka Sebagai Peningkatan Mutu Pendidikan - Muhammad Raffi Fadliansyah; Hindun Hindun (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2023)
The independent curriculum is a restoration of the 2013 curriculum which was previously implemented in educational institutions in Indonesia. Currently, the restoration of the curriculum to an independent curriculum is due to the need for students to be able to improve the quality of education in Indonesia. With advances in technology, of course the role of an independent curriculum is also very important to collaborate in improving the quality of education in Indonesia. The aim of this research is to find out the role of technology as supporting the success of implementing an independent curriculum in schools, apart from that it also wants to see what are the obstacles to collaborative technological progress in the education system. This research that uses qualitative descriptive analysis produces detailed and clear analysis. In collecting data, researchers use library research by looking at various sources that are relevant to the research. The data analysis technique goes through several steps, namely data collection carried out by researchers by grouping data arranged in narrative form, then data reduction, namely collecting important data from the information found and in accordance with the problem topic, then presenting the data with narrative explanations that are strengthened from the study. literature, and finally draw conclusions.